Foot Care Interventions for Patients with Type 2 Diabetes Mellitus Through A Home-Based and Family Involvement Approach - Prajayati Era (PT. AVID MEDIA INDONESIA, 2026)
Type 2 diabetes mellitus is a chronic disease that can lead to serious complications, one of which is diabetic foot ulcers. Home-based foot care interventions involving families are considered an effective approach to improving care outcomes and preventing complications. Objective: This study aimed to review and synthesize scientific evidence regarding the effectiveness of home-based foot care interventions and family involvement in patients with type 2 diabetes mellitus. Methods: This study used a literature review design with a PICO approach. Articles were obtained from PubMed, ScienceDirect, and Google Scholar databases using the keywords: